African same-sex sexualities and gender diversity: A framing note. (February 2021) - Reddy, Vasu; Sandfort, Theo
This article introduces the concept of African same-sex sexualities and gender diversity which refers to variation pertinent to gender expressions and identities, sexual expression and sexual orientation. The article describes the emerging and evolving African scholarly production evident in the last two decades and explains key underlying themes that bring together this special issue.